It is 2a-b simplified
Add them together: 2a+5a = 7a
2a² + 6a
2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1
9a + 1
5a + 11
2a + 4b
2a + 3a + 4 = 5a + 4
2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8
2a + 11a - 5a = 8a
5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.
a + 7b + 2c
There are no like terms here.
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
a + a + a - 2a = 3a - 2a = a
4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]
2a + a = 3a
2a+3b+4c cannot be added. They are not like terms. Like terms need to have the same variable in order to be added.
5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)
What is the solution of -2a plus 3a plus 5b